ANALYSIS OF STUDENTS' LEARNING STYLES IN ISLAMIC EDUCATION LESSONS AT KARTIKA LIMA (V) ELEMENTARY SCHOOL IN IMPROVING ACADEMIC ACHIEVEMENT - Heriyanita Rosmini; Ningsih Ningsih; Adiyono Adiyono (Adisam Publisher, 2025)
This study aims to analyze students' learning styles in Islamic Religious Education (PAI) lessons at Kartika Lima Elementary School (V) and their relationship with improving academic achievement. Learning style is one of the important factors that influence students' success in understanding subject matter. This research used a descriptive qualitative approach with data collection methods through interviews, observations, and document studies. The research subjects were fourth and fifth grade students and PAI teachers. The results showed that students have various learning styles, including visual, auditory, and kinesthetic learning styles. The selection of learning methods that suit students' learning styles is proven to improve their understanding of the material, thus having a positive impact on academic achievement. This finding indicates that PAI teachers need to adapt varied and inclusive learning strategies to meet the needs of students' learning styles. This research is expected to be a reference for educators in optimizing students' potential through appropriate learning approaches, as well as contributing to the development of effective PAI learning strategies at the elementary school level.